An Assessment of Safety Culture While Navigating Work Zones: Attitudes and Behavior Toward In-Vehicle Messaging Technologies. (September 2016) - Achtemeier, Jacob D.; Morris, Nichole L.
A survey was administered to evaluate a variety of driver opinions, behaviors, and technology use in the context of work zones. Safety culture thematic inquiries, such as willingness to use a cell phone while driving, as well as adherence and trust of conventional work zone signage were included in the driver behavior inventory. Thematic results were examined through a factor analyses, providing insight into the relationship among responses to survey items. Study results contribute to the understanding of driver attitudes towards conventional signage in work zones, driver perceptions of their and others' safety, and the degree to which drivers are receptive to new in-vehicle technologies to supplement signage. Driver attitudes and reported interactions with phones while driving is discussed. The study explores the safety and acceptance potential of an in-vehicle, smartphone-based, work zone messaging system on driver behavior and roadway safety.